2011
DOI: 10.1186/1475-2840-10-44
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased plasma adipocyte fatty acid-binding protein with coronary artery disease in non-elderly men

Abstract: BackgroundAdipocyte fatty acid-binding protein (A-FABP) has been reported to play critical roles in the development of atherosclerosis. We investigated whether an increased in plasma A-FABP level can be independently associated with the presence of coronary artery disease (CAD).MethodsTwo hundred eleven consecutive male patients (mean age: 66 years, range: 33-87 years) were enrolled from inpatients who underwent coronary angiography. Age-matched male subjects (n = 211) having no evidence of CAD served as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
7
23
0
Order By: Relevance
“…Furthermore, AFABP concentrations significantly increase with the number of stenotic coronary arteries [75]. In accordance with these findings, three independent studies have reported that serum AFABP is significantly elevated in patients with coronary artery disease (CAD) [76][77][78]. Very recently, a small casecontrol study detected significantly elevated serum AFABP levels in patients with cerebrovascular disease, whereas no difference was found in patients with CAD [79].…”
Section: Controlssupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, AFABP concentrations significantly increase with the number of stenotic coronary arteries [75]. In accordance with these findings, three independent studies have reported that serum AFABP is significantly elevated in patients with coronary artery disease (CAD) [76][77][78]. Very recently, a small casecontrol study detected significantly elevated serum AFABP levels in patients with cerebrovascular disease, whereas no difference was found in patients with CAD [79].…”
Section: Controlssupporting
confidence: 53%
“…Furthermore, murine adipocytes release various proteins lacking a secretory signal sequence by microvesicles and, most interestingly, AFABP is detected in microvesicles [64]. These findings are supported by an independent study that [73] 98 CAD Associated with MS + TG [74] 479 with carotid IMT Associated with IMT in women + Age, BP, carotid IMT (in women) [75] 234 with coronary angiograms Associated with CAD n.d. [76] 211 CAD ↑ in CAD + CAD 211 controls [77] 125 CAD ↑ in CAD + Plaque volume (CAD) 120 controls [78] 247 CAD ↑ in CAD + Coronary atherosclerosis index 94 controls [79] 18 CAD/CVD ↑ in CVD n.d. 18 controls [80] 87 controls Associated with vascular inflammation + Vascular inflammation [90] 306 acute ischaemic stroke ↑ in ischaemic stroke n.d.…”
Section: Circulating Afabp-a Potential Novel Adipokinementioning
confidence: 99%
“…For instance, circulating FABP4 correlated positively with carotid intima-media thickness in Chinese women, 20 with atherosclerotic burden measured by intravascular ultrasound, 21 or with CAD in nonelderly Japanese men. 22 These discrepant findings between white and Asian populations on the association of circulating FABP4 with CAD might be partially explained by different genetic and environmental background. For instance, the prevalence of hypertension, hypercholesterolemia, or overweight and obesity is higher in whites than in Asians.…”
Section: Discussionmentioning
confidence: 96%
“…6,11-18 Notably, an increased plasma level of FABP4 was shown to be independently associated with the presence of coronary artery disease. 19, 20 Moreover, FABP4 has been found in human atherosclerotic plaques, and its presence was associated with the features of inflammatory and vulnerable plaques as high-risk phenotypes. 19,21 F atty acid-binding proteins (FABPs) are a family of intracellular lipid chaperones, approximately 14-15-kDa predominantly cytosolic proteins that can reversibly bind hydrophobic ligands such as saturated and unsaturated long-chain fatty acids.…”
mentioning
confidence: 99%